Does the Use of Potential Pancreatotoxic Drugs Increase the Risk of Post-Endoscopic Cholangiopancreatography Pancreatitis? - Wilson Siu; Hasib Ahmadzai; Muhammad Haziq Hasnol; Muhammad Nabil Fauzi; Ash Li Khoo; Muzhi Zhao; Andrew Thomson (Gastroenterology Insights)
Background and Aim: Endoscopic retrograde cholangiopancreatography (ERCP) is a valuable procedure for pancreatobiliary disorders but carries significant risks, including post-ERCP pancreatitis (PEP). The exact cause of PEP is unclear, but mechanical and thermal injuries during the procedure and patient-related factors have been implicated. This study aims to investigate the possible contribution of potential pancreatotoxic drug (PPD) exposure to PEP risk. Methods: This was a retrospective, single-centre, cohort study conducted at Canberra Hospital, a tertiary university hospital. Consecutive ERCP performed with native papillae within a 4-year period from January 2019 to January 2023 were evaluated. Details of ERCP procedures, patient characteristics, and all medications were contemporaneously collected. All patients had follow-up phone calls or review within 24 h post procedure. The diagnosis of PEP was based on the Cotton consensus definition. Results: A total of 32 out of 444 patients (7.2%) developed PEP. There was no significant difference in the incidence of PEP between patients taking PPD compared to patients who were not (7.1% vs. 7.6%, p = 0.845). Three factors were independently associated with PEP in the multivariate analysis: the presence of a periampullary diverticulum (OR = 5.4, 95% CI 1.7–15.3, p = 0.002), the performance of pre-cut sphincterotomy (OR = 2.8, 95% CI 1.2–6.4, p = 0.017), and pancreatic duct cannulation (OR = 3, CI 1.3–7, p = 0.01). Conclusions: The overall incidence of pancreatitis in our selected group of ERCP patients with native papillae was 7.2%. Our study did not find the use of PPD to be a statistically significant risk factor for PEP.